The Impact of Islamic Bank Mergers on the Performance of the Islamic Banking Industry Using the Structure Conduct Performance (SCP) Method - Nafis, Runanda Fachri; Purnomo, Hadi; Anwar, Eng. Saiful (International Journal of Economics Development Research (IJEDR), 2024)
This study seeks to examine the impact of the merger of three Islamic banks (BSM, BNIS, and BRIS) on the Islamic banking market in Indonesia by applying the Structure-Conduct-Performance (SCP) model. The SCP framework, widely used in economic analysis, evaluates industries based on three key dimensions: Structure, Conduct, and Performance. This research employs a quantitative approach, utilizing secondary data sourced from the annual reports and financial statements of Indonesian Islamic banks between 2017 and 2022, alongside the Islamic Financial Development Reports published by the Financial Services Authority (OJK) during the same period. The findings reveal that the merger has no discernible effect on the market structure within the Islamic banking sector in Indonesia. Additionally, the merger does not influence market conduct or consumer behavior within the industry. However, the performance of the merged banks shows a significant positive impact on the overall performance of the Islamic banking industry in Indonesia.